Health care providers' perspectives regarding the use of chlorhexidine gel for cord care in neonates in rural Kenya: implications for scale-up - Angela Muriuki; Francis Obare; Bill Ayieko; Dennis Matanda; Kenneth Sisimwo; Brian Mdawida (BMC, 2017)
Abstract Background This paper explores the perspectives of health care providers regarding the use of 7.1% Chlorhexidine Digluconate (CHX) gel that releases 4% chlorhexidine for newborn umbilical cord care under a managed access program (MAP) implemented in Bungoma County of Kenya. Understanding the perspectives of providers regarding CHX is important since they play a key role in the health system and the fact that their views could be influenced by prior beliefs and inconsistent practices regarding umbilical cord care. Methods Data are from in-depth interviews conducted between April and June 2016 with 39 service providers from 21 facilities that participated in the program. The data were transcribed, typed in Word and analyzed for content. Analysis entailed identifying recurring themes based on the interview guides. Results Use of CHX gel for cord care in neonates was acceptable to the health care providers, with all of them supporting scaling up its use throughout the country. Their views were largely influenced by positive outcomes of the medication including fast healing of the cord as reported by mothers, minimal side effects, reduced newborn infections based on what their records showed and mothers' reports, ease of use that made it simple for them to counsel mothers on how to apply it, positive feedback from mothers which demonstrated satisfaction with the medication, and general acceptance of the medication by the community. They further noted that successful scale-up of the medication required community sensitization, adequate follow-up mechanisms to ensure mothers use the medication correctly, addressing issues of staffing levels and staff training, developing guidelines and protocols for provision of the medication, adopting appropriate service delivery approaches to ensure all groups of mothers are reached, and ensuring constant supply of the medication. Conclusion Use of CHX gel for cord care in neonates is likely to be acceptable to health care workers in settings with high prevalence of neonatal morbidity and mortality arising from cord infections. In scaling up the use of the medication in such settings, some of the health systems requirements for successful roll-out can be addressed by programs while others are likely to be a persistent challenge.